Faktor-Faktor yang Berhubungan dengan Kinerja Penyuluh Pertanian di Kabupaten Ciamis Jawa Barat - Kurniawati, Nur Puti; Sadono, Dwi; Wahyuni, Endang Sri (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2020)
Agricultural extension agent was the main spearhead in carrying out counseling. A good agricultural extension agent can be reflected in their performance. The purpose of this study were: (1) describe the characteristics of agricultural extension agent, (2) describe the level of competence, level of work motivation, and describe level of performance of agricultural extension agent, (3) analyze the relationship between characteristics of agricultural extention agent and the level of performance of agricultural extension agent, (4) analyze the relationship between the level of competency of agricultural extension agent and the level of performance of agricultural extension agent, (5) analyze the relationship between the level of motivation of agricultural extension agent and the level of performance of agricultural extension agent. Responden in this study were 48 field extension agent who are civil servant in Ciamis Regency West Java and selected by census. Data were analyzed using Rank Spearman correlation test. The results showed that agricultural extension agent in Ciamis Regency were dominated by extension agent who were old, undergraduate educated, had little training, and had a long working period. Agricultural extension agent in Ciamis Regency generally have sufficient competency which tends to be high and generally dominated by the need for achievement motivation. The results also show that there is a relationship between managerial competence and performance, social competence with performance, technical competence with performance, level of competency with performance, and the need for achievement with performance.Keywords: Agricultural Extension Agent,Competence, Motivation, Performance.